Analysis of Service Quality (Tangibles Dimension) Towards the Satisfaction of HGB Extension Applicants at the Regional Office of East Java Province - Prasetyo, Alita Safirah Prasetyo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the effect of service quality in the tangibles dimension (physical evidence) on the satisfaction of Building Use Rights (HGB) extension applicants at the East Java Provincial Office of the National Land Agency. The research method used a quantitative approach with a Likert-scale questionnaire distributed to HGB extension applicants. Data analysis was conducted using simple linear regression. The results showed that the tangibles dimension had a positive and significant effect on applicant satisfaction, as evidenced by a significance value of 0.000 (<0.05) and a regression coefficient of 0.762. The R-square value of 0.607 indicates that 60.7% of the variation in applicant satisfaction can be explained by the tangibles dimension, while the remainder is influenced by other factors outside the study. These findings confirm that improving the quality of physical evidence, such as service facilities, officer appearance, and ease of information, is a crucial factor in increasing public satisfaction with land services. This research contributes to the optimization of public services, particularly in strengthening service quality standards based on physical evidence in land agencies.